2022
DOI: 10.1039/d1cp05298e
|View full text |Cite
|
Sign up to set email alerts
|

Promising application of a SiC2/C3B heterostructure as a new platform for lithium-ion batteries

Abstract: Constructing heterostructures by the van der Waals coupling effect has provided an effective method for developing novel electrode materials. In this work, based on the first-principles calculation method, we proposed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…We further calculate the plane-averaged charge-density difference (Δρ) along the z -direction to analyze the strength of interfacial interactions, which is given by , Δ ρ = ρ interface ρ dielectric ρ SiC where ρ interface , ρ dielectric , and ρ SiC are the charge density of the interface structure, dielectric, and SiC, respectively. The strength of the interface interaction could be determined by the amplitude of the charge density difference curve.…”
Section: Resultsmentioning
confidence: 99%
“…We further calculate the plane-averaged charge-density difference (Δρ) along the z -direction to analyze the strength of interfacial interactions, which is given by , Δ ρ = ρ interface ρ dielectric ρ SiC where ρ interface , ρ dielectric , and ρ SiC are the charge density of the interface structure, dielectric, and SiC, respectively. The strength of the interface interaction could be determined by the amplitude of the charge density difference curve.…”
Section: Resultsmentioning
confidence: 99%
“…In order to further investigate the charge transfer in Ti 3 C 2 T 2 /SiC contacts, the charge-density difference between Ti 3 C 2 T 2 and SiC was investigated via calculation of the plane-averaged charge-density difference (Δ ρ ) along the z direction, which is given by 43 Δ ρ = ρ Ti 3 C 2 T 2 /SiC − ρ Ti 3 C 2 T 2 − ρ SiC where ρ Ti 3 C 2 T 2 /SiC , ρ Ti 3 C 2 T 2 , and ρ SiC are the charge density of the Ti 3 C 2 T 2 /SiC contacts, Ti 3 C 2 T 2 , and SiC, respectively. The positive and negative values of Δ ρ represent charge accumulation and depletion, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…23 Heterogeneous structures have attracted extensive attention because they can integrate the excellent properties of their components and make up for their defects. [25][26][27][28][29] For example, Minrui Yang et al found that the SiC 2 /C 3 B heterostructure has great potential to be a promising material for LIBs, because the high Li-ion capacity of SiC 2 compensates for C 3 B's relatively low capacity; 30 Guo et al found that the C 3 N/phosphorene heterostructure exhibits excellent stiffness, which is deficient in phosphorene, and good conductivities of electrons and ions, that is missing in C 3 N, indicating that C 3 N/phosphorene is a favorable anode material for LIBs; 10 a blue phosphorene/graphene heterostructure was found to be an advanced anode material for LIBs due to its remarkable mobility of Li because the fast Li diffusion of blue phosphorene remedies relatively low Li diffusion of graphene. 31 Thus, the construction of n-type C 3 N and p-type C 3 B monolayers into a van der Waals (vdw) heterostructure (C 3 N/C 3 B vdw heterostructure) might be a beneficial way to overcome the drawbacks of C 3 N (the weak Li adsorption ability) and C 3 B (low migration rate of Li).…”
Section: Introductionmentioning
confidence: 99%